2009
DOI: 10.1099/ijs.0.003210-0
|View full text |Cite
|
Sign up to set email alerts
|

Cellulophaga tyrosinoxydans sp. nov., a tyrosinase-producing bacterium isolated from seawater

Abstract: An aerobic, gliding, yellow-pigmented bacterium lacking flagella and showing strong tyrosinase activity, designated strain EM41T , was isolated from seawater on the eastern coast of Jeju Island in Korea. Growth was observed at 15-35 6C (optimum, 25-30 6C) and at pH 6.5-9.0 (optimum, pH 7.0-8.5). Cells were Gram-negative, negative for flexirubin pigments and catalase-and oxidase-positive. The G+C content of the genomic DNA was 33.5 mol% and the major respiratory quinone was menaquinone-6 (MK-6

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 18 publications
1
28
1
Order By: Relevance
“…Cell morphology and the presence of flagella were determined using phase-contrast microscopy and transmission electron microscopy (JEM-1010, JEOL) using two-day-old cells grown in MB as described previously (Jeon et al, 2004). Requirement and tolerance of NaCl were determined using nutrient broth (containing 3 g beef extract l 21 and 5 g peptone l (Kahng et al, 2009). Oxidase activity was tested by oxidation of 1 % (w/v) tetramethyl-p-phenylenediamine (Merck) and catalase activity was evaluated by the production of oxygen bubbles in 3 % (v/v) hydrogen peroxide solution (Smibert & Krieg, 1994).…”
Section: Hellea Balneolensis Dsm 19091mentioning
confidence: 99%
“…Cell morphology and the presence of flagella were determined using phase-contrast microscopy and transmission electron microscopy (JEM-1010, JEOL) using two-day-old cells grown in MB as described previously (Jeon et al, 2004). Requirement and tolerance of NaCl were determined using nutrient broth (containing 3 g beef extract l 21 and 5 g peptone l (Kahng et al, 2009). Oxidase activity was tested by oxidation of 1 % (w/v) tetramethyl-p-phenylenediamine (Merck) and catalase activity was evaluated by the production of oxygen bubbles in 3 % (v/v) hydrogen peroxide solution (Smibert & Krieg, 1994).…”
Section: Hellea Balneolensis Dsm 19091mentioning
confidence: 99%
“…4.91/82.2, respectively. These data defined the sequence of the monosaccharides and demonstrated that Fuc residue is 4-substituted, GlcNAc residue is 3-substituted, Rha 2 residue is 2-substituted while Rha 1 residue is 2,3-disubstituted and it is a branched point.…”
mentioning
confidence: 93%
“…7H 2 O, 4.53 g MgCl 2 . 6H 2 O, 0.64 g KCl and 1.3 g CaCl 2 per litre] (Kahng et al, 2009). Ionic requirements were determined using synthetic ZoBell broth with the following combinations of salts (all w/v): (i) 3.0 % NaCl; (ii) 3.0 % NaCl, 0.6 % MgCl 2 .…”
mentioning
confidence: 99%